2001
DOI: 10.1177/00131610121969415
|View full text |Cite
|
Sign up to set email alerts
|

The School Board President’s Perception of the District Superintendent: Applying the Lenses of Social Influence and Social Style

Abstract: This exploratory study used components found in social influence theory and social style to examine the school board president's perceptions of the district superintendent's ability to influence the construction of the board agenda and voting decisions made by school boards in 131 randomly chosen school districts. Social influence theory and social style suggest that credibility, social attractiveness, assertiveness, and emotiveness are effective and compelling elements of influence. Results from this study su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Cuban (1988) and Boyd (1976) argue a superintendent must collaborate with multiple stakeholder groups to ensure the community's values are reflected in the goals and outcomes of the district. Furthermore, empirical studies find superintendents' adeptness at political tasks influences the extent to which school district visions are realized (Johnson, 1996;McHenrySorber, 2014;Petersen & Short, 2001;Trujillo, 2013), as well as the length of superintendent tenure (Grissom & Andersen, 2012;Mountford, 2003). Nonetheless, superintendents spend the least amount of time on political tasks (Cuban, 1988), reporting 27% of their time devoted to this leadership dimension (Jones & Howley, 2009).…”
Section: Theoretical Framework: Superintendent Role Allocationsmentioning
confidence: 99%
“…Cuban (1988) and Boyd (1976) argue a superintendent must collaborate with multiple stakeholder groups to ensure the community's values are reflected in the goals and outcomes of the district. Furthermore, empirical studies find superintendents' adeptness at political tasks influences the extent to which school district visions are realized (Johnson, 1996;McHenrySorber, 2014;Petersen & Short, 2001;Trujillo, 2013), as well as the length of superintendent tenure (Grissom & Andersen, 2012;Mountford, 2003). Nonetheless, superintendents spend the least amount of time on political tasks (Cuban, 1988), reporting 27% of their time devoted to this leadership dimension (Jones & Howley, 2009).…”
Section: Theoretical Framework: Superintendent Role Allocationsmentioning
confidence: 99%
“…Research has consistently articulated that a poor relationship between the superintendent and the board of education deters school improvement (Danzberger et al, 1992), affects the quality of educational programs (Nygren, 1992), weakens district stability and morale (Renchler, 1992), negatively influences the superintendent's credibility, expertise, and trustworthiness with board members (Petersen & Short, 2001), impedes critical reform efforts, such as district restructuring (Konnert & Augenstein, 1995), collaborative visioning and long-range planning (Kowalski, 1999) and eventually results in an increase in the "revolving door syndrome" of district leaders (Carter & Cunningham, 1997;Renchler, 1992).…”
mentioning
confidence: 99%
“…Investigations conducted on district superintendents have attributed a variety of factors for their success or failure. Many conclude that interpersonal skills such as communication, listening, empathy, and trust are essential in the development and maintenance of a cooperative relationship between the superintendent and board of education (Berg, 1996;Bratlein & Walters, 1999;Carter & Cunningham, 1997;Glass, 1992;Kowalski, 1999;McCurdy, 1992;Petersen & Short, 2001;Tallerico, 1989;Yukl, 1994). Glass, Björk, and Brunner (2000) reported that superintendents judged as exemplary leaders spend twice as much time as their counterparts in meeting and communicating with board members.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have identified important areas related to enhancing the relationship between governing boards and executives (Petersen & Short, 2001;Piland, 1994;Polk, LaCombe, & Goddard, 1976;Potter & Phelan, 2008;Weisman & Vaughan, 1997a). The human nature of these relationships cannot be ignored (Piland, 1994).…”
Section: Characteristics and Issues Affecting Board-president Relatiomentioning
confidence: 99%